EFFECT OF DIFFERENT SUPPLEMENT ON DEGRADATION OF DRY MATTER AND FIBER OF UNTREATED AND UREA TREATED RICE STRAW IN THE RUMEN OF SHEEP - Yulistiani, D.; Jelan, Z.A.; Liang, J.B.; Abdullah, N. (Diponegoro University, 2011)
The study was conducted to investigate the degradation of dry matter (DM) and neutral detergentfiber (NDF) of urea untreated (URS) and urea treated rice straw (TRS) incubated in the rumen of sheepfed different diet. Three fistulated sheep were fed on urea-treated rice straw basal diet with threesupplemental treatment diets which consisted of control diet (T0) mulberry and molasses; mulberry,rice bran and urea (T1); and rice bran and urea (T2). Either URS or TRS was placed in nylon bags andincubated in the rumen at 0, 8, 16, 24, 48 and 72 hours. Parameters recorded were degradation of DMand NDF, rumen pH, rumen ammonia. The results showed that DM degradability of URS of the diet T1was significantly lower than other diets. Similarly the URS degradability of rumen-insoluble fraction(b) of DM and NDF of T1 diet was significantly lower than those of T0 and T2 diet. DM and NDFdegradability of URS was not affected by diets. The rumen ammonia concentration of T1 and T2 wassignificantly higher than those T0, but still higher than critical ammonia concentration required forrumen microbial synthesis. These results suggest that different supplementations have no significanteffect on DM and NDF degradability of TRS.